Vaginal Birth after Cesarean Section in Iran: A Narrative Review - Roghayeh Pakdaman; Mahboobeh Firoozi (Mashhad University of Medical Sciences, 2021)
Background & aim: Vaginal birth after cesarean (VBAC) is a global solution to reduce the number and complications of repeat cesarean section (C-section); however, fear of consequences is an obstacle preventing its performance. Knowledge of research available in each country provides the support needed for making decisions regarding evidence-based actions for healthcare service providers in the country. This study aimed to review the studies performed to investigate VBAC in Iran. Methods: Search was carried out on Engliah and Persian databases including PubMed, Scopus, Google Scholar, Magiran, and SID. Retrieved articles up to October 2020 were included in the review and the search process was performed using the keywords of "Vaginal birth after cesarean", "Repeat C-section", "Trial of labor after C-section", "VBAC", and "TOLAC". All related studies without time restriction were entered into the study, resulting in a total of 12 studies. Results: The success rate of VBAC varied from 27%-91.2% in different parts of Iran between 1981 and 2020. Moreover, maternal and neonatal adverse outcomes and cost and length of hospitalization were lower in the VBAC group. No related maternal death was reported in all reviewed studies. Conclusion: The findings of the present review indicated the lack of access to sufficient study resources on this field of research in Iran. Nevertheless, it is required to employ strategies as building an organizational culture, clinical contextualization at the level of healthcare services, and improving service environments, including VBAC supportive centers to promote this practice in the country.